A meta-analysis of the effectiveness of park-and-ride facilities - Zijlstra, Toon; Vanoutrive, Thomas; Verhetsel, Ann (European Journal of Transport and Infrastructure Research, 2015)
In this paper we present a meta-analysis of Park-and-Ride (P+R) facilities. Our goal is to identify the determinants of effective sites and to assess their contribution with respect to various transport policy objectives. An effective facility predominantly attracts target group users, i.e. users who without the P+R would use the car for the entire journey. Our meta-analysis is based on the results of 40 studies and a total of 180 evaluated P+R sites, mainly from European countries. Linear regression analysis is used to estimate the influence of seven explanatory variables. Public transport mode and point of intercept are identified as the most important factors. The share of commuters, weekday or weekend use and the number of parking spaces have a significant, but limited influence on the effectiveness. The statistics from the dataset and the linear regression results are used to calculate the effects on three main policy objectives. Our analysis indicates that P+R facilities with a destination function intercept about 47 cars per 100 parking spaces provided. Public transport use drops slightly and private car kilometres (to reach the P+R) increase. Facilities with an origin function intercept about 21 cars per 100 parking spaces, private car kilometres are slightly reduced and kilometres in public transport use increases. Our results are useful to assess the impact of future P+R interventions and to formulate regional P+R policies.